Kesulitan Guru IPA SMP se-Kecamatan Enggal dalam Merencanakan dan Melaksanakan Asesmen - Reza Tihardila; Rini Rita T Marpaung; Arwin Achmad (Universitas Lampung, 2018)
This study aimed to identify the difficulties of science teachers in planning and implementing out the assessment. The research design was simple descriptive design. The samples of this research were 30 science teacher at Enggal sub-district of Bandar Lampung that were selected by total sampling technique. Data difficulties of science teachers in planning and implementing the assessment obtained from questionnaires, interviews and teacher profile information then analyzed descriptively. The result of the research showed that the average of teachers difficulties in planning the assessment was high of 63% ± 16. The teachers difficulties in implementing the assessment was enough of 47% ± 2. The highest difficulty in planning the assessment was on indicators determine the technique and forms of assessment. While the highest difficulty in implementing out the assessment was the psychomotor. Penelitian ini bertujuan mengidentifikasi kesulitan guru IPA dalam merencanakan dan melaksanakan asesmen. Desain yang digunakan pada penelitian ini adalah desain deskriptif sederhana. Sampel penelitian adalah guru IPA SMP se-Kecamatan Enggal Bandar Lampung berjumlah 30 guru yang dipilih dengan teknik total sampling. Data kesulitan guru dalam merencanakan dan melaksanakan asesmen diperoleh dari angket, wawancara dan informasi profil guru kemudian dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa kesulitan guru dalam merencanakan asesmen dikategorikan tinggi sebesar 63% ± 16. Kesulitan guru dalam melaksanakan asesmen dikategorikan cukup sebesar 47% ± 2. Kesulitan tertinggi dalam merencanakan asesmen yaitu pada penentuan teknik dan bentuk asesmen. Sementara kesulitan tertinggi dalam melaksanakan asesmen yaitu pada ranah psikomotorik Kata kunci: asesmen, guru IPA, kesulitan, melaksanakan, merencanakan